2015
DOI: 10.1089/jir.2014.0197
|View full text |Cite
|
Sign up to set email alerts
|

Successful Interferon Therapy Reverses Enhanced Hepatic Progenitor Cell Activation in Patients with Chronic Hepatitis C

Abstract: The enhanced accumulation of hepatic progenitor cells (HPCs) is related to the risk of progression to hepatocellular carcinoma (HCC). Interferon (IFN) treatment reduces HCC risk in patients with chronic hepatitis C virus (HCV) infection. However, the underlying mechanisms remain unclear. The aim of this study was to examine the effects of IFN treatment on HPC activation in HCV patients. Immunohistochemical detection and computer-assisted quantitative image analyses of cytokeratin 7 (CK7) were performed to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
(6 reference statements)
2
3
0
1
Order By: Relevance
“…The current study confirmed previous reports that demonstrated HPCs in HCV-infected liver biopsies in the form of DR as well as IPCs18,33 . More importantly, we found that responders (SVR) had a significantly lower number of HPCs (both DR and IPCs) than non-responders (Non-SVR).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The current study confirmed previous reports that demonstrated HPCs in HCV-infected liver biopsies in the form of DR as well as IPCs18,33 . More importantly, we found that responders (SVR) had a significantly lower number of HPCs (both DR and IPCs) than non-responders (Non-SVR).…”
Section: Discussionsupporting
confidence: 92%
“…Another important observation in the present study was that the number of HPCs was significantly higher in later stages of fibrosis. This confirms several previous studies9,10,17,18 and indicates that HPCs participate either directly or indirectly through cross talk with stellate cells in the process of hepatic fibrogenesis. We investigated the relationship between stellate cells and HPCs in chronic HCV in a previous report36.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations